Patient Characteristics, Procedural Details, and Outcomes of Contemporary Percutaneous Coronary Interventions - Kashif Ullah Shah, Irfan Ali Khan, Zia Ur Rehman, Qazi Najeeb Ullah Amin, Farman Ullah, Sami Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The prevalence and success of percutaneous coronary intervention (PCI) varies widely between regions, with South Asia displaying some of the greatest regional differences. Objectives: Examining PCI procedures and their outcomes in Pakistan over time and comparing this information to that from other countries is the goal of this study. Methods: Throughout the course of a year, information was collected from several cardiac catheterization laboratories in Pakistan. An in-depth history of each patient was recorded, along with data on their procedures, the tools and drugs they required, their outcomes, and any complications that may have arisen. Results: The study contained information from 22,741 patients. Their average age was 64.2 years (11.7) and they were predominantly male (70%). Acute coronary syndrome was the most prevalent symptom (57%), while ST-elevation myocardial infarction was the most common type of heart attack (28%). Multivessel disease was present in nearly two-thirds of patients, and 11% of those patients also had substantial left main stenosis. Almost half of these procedures (44.2%) opted for the transradial route. In spite of the high complexity of the lesions (56.9% class C lesion), the operative success rate was quite good at 95.2%. There was a 5.3% rate of procedure-related complications and a 2.8% rate of in-hospital deaths. Conclusion: The collected data shed light on the state of PCI in the United States, both in terms of its implementation and its results. Despite the complexity of the lesions being treated, the success rate was high, and problems were minimal.